Faktor-Faktor yang Berhubungan Dengan Kinerja Tenaga PKIP di Provinsi DKI Jakarta - Nadra Dinamara; Sarah Handayani; Handayani (Universitas Cokroaminoto Yogyakarta, 2026)
Health Promotion is effort For increase ability public through learning of , by, for , and together society, so that they can help himself yourself, as well develop sourced activities _ Power society, accordingly social culture local and supported by policy health - minded public. The purpose of study This is for know performance power promotion health in DKI Jakarta Province in 2022. Research This nature analytic with design study cut latitude (cross sectional) research instrument use questionnaires and interviews, Chi Squre test results showing No There is significant relationship _ level education p-value- 0.369 α < 0.05. position with performance power Health promotion p-value 0.933 α >0.05, Chi Square Test results showing There is connection income p-value 0.015 α <0.05. Training p-value 0.032 α <0.05. knowledge p-value 0.004 α <0.05. attitude p-value 0.033 α <0.05, Media/Kie p-value 0.009 α <0.05, with performance power Health promotion, meanwhile Skills empowerment community, advocacy and networking partnership No There is significant relationship _ with performance power Health promotion α value >0.05, variable multivariate analysis test results income, knowledge and media/KIE skills are very influential to performance power promotion health and science Behavior in DKI Jakarta Province p-value < 0.25. Research result This Can made as reference in designing something policy in an effort to improve performance power promotion of Health and science behavior in DKI Jakarta Province.